Competing Maritime Interests in the South China Sea: Asian Geopolitical Implications - Kunkunrat Kunkunrat (Jurnal Restorasi : Hukum dan Politik, 2023)
The South China Sea, as a strategic route for international trade and a rich natural resource area, is at the center of tensions between countries in the region. This research will analyze the root causes of conflict, the strategies used by regional and global actors to advance their interests, and the geopolitical implications for stability and security in Asia. This research uses a qualitative approach with descriptive methods. The research results show that global maritime power competition in the South China Sea has a significant impact on Asian geopolitics. Regional tensions, economic uncertainty, changes in global security dynamics, environmental damage, diplomatic and international legal challenges, strategic uncertainty, impacts on energy security, as well as increased military activity and weapons are direct consequences of this competition. This underscores the need for collaborative efforts, multilateral dialogue and sustainable policies to manage and mitigate negative impacts, while promoting stability in the South China Sea region.